Domain-specific Consideration of Future Consequences: Further Evidence Using Academic Attainment Data. Issue 4 (2nd October 2022) - McKay, Michael T.; Perry, John L.; Worrell, Frank C.; Cole, Jon C.
ABSTRACT: A number of recent studies have demonstrated that adolescents consider the future consequences (CFC) of behaviours domain-specifically. In other words, rather than being a "future orientated person, " it appears that the orientation varies within individuals, depending on the domain in question. The present study matched data gathered in Scottish school children ( N  = 451) on consideration of four future domains (Health and Well-being, Finances, Academics, and Global Warming) with sociodemographic and academic attainment data provided by Local Government. Results showed that deprivation was significantly related to academic attainment, and that this relationship was partially mediated by the combined effects of academic self-efficacy and on consideration of future consequences—academic. Further, domain specificity was supported by the fact that scores for consideration of future consequences—health and well-being, —finance, and—global warming did not partially mediate the deprivation-attainment relationship. The study identifies two variables which may contribute to closing the poverty-related attainment gap.